2010
DOI: 10.1103/physreve.82.046401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prepulse on fast electron lateral transport at the target surface irradiated by intense femtosecond laser pulses

Abstract: The effects of preplasma on lateral fast electron transport at front target surface, irradiated by ultraintense (>10(18) W/cm2) laser pulses, are investigated by Kα imaging technique. A large annular Kα halo with a diameter of ∼560 μm surrounding a central spot is observed. A specially designed steplike target is used to identify the possible mechanisms. It is believed that the halos are mainly generated by the lateral diffusion of fast electrons due to the electrostatic and magnetic fields in the preplasma. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This phenomenon can be attributed to the increase in the x-ray source size resulting from the lateral transport of fast electrons at higher laser intensities. [28][29][30] Other researchers have also found that the size of the Kα source increases with the laser intensity. [31][32][33] The spatial resolution of the backlight system depends on the imaging crystal, the x-ray detectors, and the backlight source, etc.…”
Section: Investigation Of Backlighter Intensity and Spatial Resolutio...mentioning
confidence: 93%
“…This phenomenon can be attributed to the increase in the x-ray source size resulting from the lateral transport of fast electrons at higher laser intensities. [28][29][30] Other researchers have also found that the size of the Kα source increases with the laser intensity. [31][32][33] The spatial resolution of the backlight system depends on the imaging crystal, the x-ray detectors, and the backlight source, etc.…”
Section: Investigation Of Backlighter Intensity and Spatial Resolutio...mentioning
confidence: 93%